Unconventional monetary policy and money demand - Christian Dreger; Jürgen Wolters (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper investigates the usefulness of the money demand relationship in times of unconventional monetary policies by cointegration methods. In contrast to the bulk of the literature, evidence in favour of a stable long run money demand function is presented both for the US and the euro area. Results are based on standard monetary aggregates, i.e. MZM for the US and M3 in case of the euro area. The recent monetary policy shifts towards unconventional measures did not introduce instability in the relationships. The results suggest that money balances are still useful instruments to conduct monetary policy especially in periods where the nominal interest rates are at the zero lower bounds.
Keywords: C22; C52; E41; 330; unconventional monetary policy; money demand; stability